SUN-542 The Effect of Energy Deprivation on Metabolic Hormone Responses to Meals - Shekhar, Skand (J Endocr Soc, 2020)
Background: Intermittent caloric restriction (ICR) has recently gained popularity as a weight-loss strategy; however, fasting metabolic hormones and dynamic meal-related responses, are not well-established in this setting. Methods: We measured metabolic hormone responses to 5-days of neutral or decreased energy availability (NEA, 45 kcal/kg LBM*d vs DEA, 20 kcal/kg LBM*d) in the early follicular phase (EFP) in 19 regularly-cycling, sedentary, women (age 23.36± 2.08 yr; mean±SD). Hunger was assessed using a visual analogue scale on the 5(th) day of each condition. Scheduled breakfast and lunch were administered according to assigned caloric intake, while an afternoon snack based on NEA was provided on both occasions. Blood was sampled for leptin, insulin, glucose, and GH at 10-min intervals and cortisol was measured at 30-min intervals over eight hours starting at 0800 h, while Orexin A and adiponectin were measured in fasting samples. AUC for each hormone for every meal and diet condition were analyzed using linear mixed models. Insulin and insulin/glucose ratio (I/G) were also adjusted for meal calories. Percentage body fat mass was measured every visit using air displacement plethysmography (BodPod®). Results are presented as least square mean ± sem. Results: There were no differences in body mass index or % fat mass after NEA vs DEA although there was a significant increase in hunger with DEA (p=0.002). Fasting levels of glucose and insulin were unchanged while leptin decreased with DEA (1.27±0.07 and 1.04±0.07 ng/mL, NEA and DEA respectively; p<0.0001), and Orexin A increased (0.55±0.04 and 0.60±0.04 ng/mL; p=0.04). The AUC for glucose was lower with DEA across all meals (p<0.0001). Insulin, I/G and I/G normalized for ingested calories (nI/G) decreased in response to DEA (p<0.005, p<0.05 and p<0.0001). The slope of the increase in leptin across the day was not different between NEA and DEA (p=0.20). Adiponectin, GH and cortisol were unaffected by DEA. Conclusion: These studies indicate that although fasting glucose and insulin are unaffected by short-term caloric restriction, the insulin response to glucose is attenuated even when adjusting for meal-related calories. Orexin A increased and leptin decreased with reduced caloric intake, acting, at least in part, to stimulate appetite. Taken together, these hormonal responses, directed at preserving energy homeostasis, have important implications for understanding the potential efficacy of intermittent caloric restriction.